Towards Recency Ranking in Community Question Answering - A Case Study of Stack Overflow - Amancio, Leandro; Dorneles, Carina Friedrich (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
In Community Question Answering, recency ranking refers to put the freshness answers with high quality in top positions of a ranking. Freshness is not related to how recent is the answer creation date, but to how up-to-date is the answer content. This is extremely important because the users need to get best answers quickly to solve their questions and, usually, they expect up-to-date solutions. In this paper, we propose a new approach to provide recency ranking in these environments and present a set of experiments that show the effectiveness of our proposal.